Sistem Pencarian Rute untuk Salesman menggunakan metode Saving Matrix dengan Harmony Search pada Android - Lukas Fernando Hunggianto; Kartika Gunadi; Anita Nathania Purbowo (Jurnal Infra, 2021)
Technology is growing at faster rate. Smartphone usage becomes one of the requirements to do many kinds of things. The majority of smartphone users currently using Android because it has a affordable price. Global Positioning System Technology (GPS) nowadays is easy to use can be applied to many things. One of them is application of tracking device. In the PT. X. , this technology can be used to do product review after-sales. Sales at the PT. X has a job that has been given by their supervisor to do product identification for their installed GPS device. This product that need to be identified is widely spread in Indonesia. For this research, they are using perfected saving matrix method using harmony search to produce short distance travel. At testing it will be compared between only saving matrix, harmony search, and both of the saving matrix and harmony search. The results obtained all the features can run well. The route calculation using the saving matrix method with harmony search gets test results in area 1 with 34 destination points, the average saving is 4.163%, while in area 2 with 38 destination points, the average savings is 1.789%.